Assessing expectations of European house prices - Akhilesh Kumar Verma; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2024)
Using a new database of consumers expectations, this paper examines the nature of house price forecasts across a select sample of European Union (EU) member states for the period 2020 to 2024. Across many EU countries, post Covid-19, house price increases have been apparent. Therefore, understanding the dynamics of house price movements is especially important at this time. In particular, we examine the rationality or otherwise of consumers house price expectations and then examine the relationship between the expectations and those forecasts of key fundamental determinants of house prices such as interest rates and income levels. In this way we distinguish our work from most other studies of house price forecasts which have not examined links between house price forecasts themselves and forecasts of the variables typically assumed to be determining prices. This is particularly relevant as often times house price expectations themselves are influenced by changes in market fundamentals.
Keywords: D84; G12; R21; 330; House prices; forecasting bias; fundamental variables